MENGESTIMASI EFEK KEBIJAKAN DIVIDEN DAN HARGA SAHAM TERHADAP NILAI PERUSAHAAN DI JAKARTA ISLAMIC INDEKS - Hesi Eka Puteri (UIN Sunan Gunung Djati Bandung, 2023)
This study analyzes the effect of Dividend Policy and Stock Prices on Firm's Value listed on the Jakarta Islamic Index in 2017-2021. The issue of firm's value and its determinants is an important study in the Jakarta Islamic Index, due to the growing enthusiasm for sharia stocks listed on the Jakarta Stock Exchange. The data in this study is secondary data obtained from the Jakarta Islamic Index, with a total sample of 13 companies registered in the 2017-2021 analysis period. Panel data regression is used in this study by selecting the Fixed Effect (FE) Model as the estimation method. Findings have revealed that firm value is influenced by stock prices (closing price), but dividend policy has no effect on firm value. As much as 25.99% of the variation in firm's value achievements can be explained by dividend policy and stock prices, while 74.01% is explained by other factors outside the model. An increase in stock prices can increase firm's value positively. An increase in stock prices can increase firm's value while dividend policy is not proven to be able to increase firm's value as measured by Price To Book Value. These findings have practical implications for policy makers, especially for companies listed on the Jakarta Islamic Index in order to maintain good control over financial decisions and stock prices because they affect firm value. The stock price is a reference for investors to decide to invest because the stock price shows the performance of the issuer.